Project’s name auditing accounts receivable in the process of auditing financial statement at Thang long -T.D.K auditing and valuation limited company - Ha, Thi Thanh Huyen (H. : ĐHQGHN, 2020)
This paper study the process of auditing accounts receivable from customers at Thang Long - T.D.K Company. The objective of this research is to focus on Thang Long “ T.D.K Company and a specific case of BeeaHN Vietnam Co., Ltd. A significant bulk of the paper is dedicated to the process of auditing accounts receivable from customers in general, and the process of auditing accounts receivable from customers for a specific customer in particular performed by Thang Long - T.D.K Auditing and Valuation Co., Ltd. In addition, interviewees and researcher recognized the advantages of auditing customer receivables from customers at Thang Long - T.D.K Auditing and Valuation Co., Ltd as follows: young, dynamic, enthusiastic and highly qualified staffs, audit records are stored scientifically, as well as quality control is always focused. In addition to the above advantages, the author found some remaining limitations in the audit process at Thang Long - T.D.K Auditing and Valuation Co., Ltd on human resources is limited before the workload in the market. Auditing programs have not been designed and built specifically for each specific type of business, as well as the implementation of tests of detailed procedures still largely depends on the auditor’s judgment.